Wear-Resistant Nanostructured Sol-Gel Coatings for Functional Applications - Felde, Nadja; Coriand, Luisa; Duparré, Angela; Tünnermann, Andreas (Journal of Coating Science and Technology, 2016)
Improvement of the wear resistance of functional surfaces is crucial in order to facilitate a variety of practical applications, such as self-cleaning or anti-fogging. This especially holds for functional surface nanostructures, whose tops can easily get worn off when exposed to even low abrasion forces. Thus, our work addresses the enhancement of the wear resistance of such fine-scale structures. We present an efficient manufacturing procedure for generating long-term durable surfaces with simultaneously tailored wetting behavior and high optical quality. Our approach is based on a sol-gel coating that consists of an alumina layer with specific nanoroughness yielding the function-relevant surface structure, and a protective thin smooth silica film providing the mechanical robustness without influencing that functional structure. The roughness of the alumina layer can be systematically adjusted, thus enabling us to achieve desired wetting effects all the way up to superhydrophilicity and, after application of an additional thin hydrophobic top coat, to superhydrophobicity. To demonstrate the enhanced robustness of these coatings we perform abrasive wear tests and investigate the impact of abrasion cycles on the wetting effects and optical properties of the coatings. Furthermore, the durability of the structures is directly revealed by advanced roughness characterization procedures based on Atomic Force Microscopy followed by power spectral density function (PSD) analysis.